Using forward contracts to reduce regulatory capture - Felix Höffler; Sebastian Kranz (Max Planck Institute for Research on Collective Goods, 2011)
A fully unbundled, regulated network firm of unknown efficiency level can undertake unobservable effort to increase the likelihood of low downstream prices, e.g., by facilitating downstream competition. To incentivize such effort, the regulator can use an incentive scheme paying transfers to the firm contingent on realized downstream prices. Alternatively, the regulator can propose to the firm to sell the following forward contracts: the firm pays the downstream price to the owners of a contract, but receives the expected value of the contracts when selling them to a competitive financial market. We compare the two regulatory tools with respect to regulatory capture: if the regulator can be bribed to suppress information on the underlying state of the world (the basic probability of high downstream prices, or the type of the firm), optimal regulation uses forward contracts only.
Keywords: K23; L94; L43; L51; 330; incentive regulation; regulatory capture; virtual power plants; Anreizregulierung; Termingeschäft; Elektrizitätswirtschaft; Lieferanten-Kunden-Beziehung; Theorie